Open pleural decortication in a 12-day-old neonate with empyema thoracis - Medjo, Biljana; Vujović, Dragana; Atanasković-Marković , Marina; Karličić, Marija; Radović, Tijana; Nikolić, Dimitrije (Vojnosanitetski pregled, 2023)
Introduction. Empyema thoracis, defined as the accumulation of pus in the pleural space, is rare in the neonatal population. Limited data are reported in the medical literature, and still, no treatment guidelines are available for this age. Case report. We present a term 12-day-old neonate (born healthy) who developed sepsis caused by methicillin-resistant Staphylococcus aureus (MRSA) and pneumonia associated with advanced-stage empyema. The child was admitted to our hospital with a few-hours history of difficulty breathing and lethargy. On admission, the child was cyanotic with desaturation and in severe respiratory distress; therefore, the child was intubated, and mechanical ventilation was started. Imaging tests were performed in an emergency, hence chest computed tomography (CT) scan was done without contrast. Suspected congenital pulmonary airway malformation with trapped air collections, significant mediastinal shift on CT scan, and deterioration of the patient’s condition indicated urgent surgery. Intraoperatively, the diagnosis of stage II empyema was established, and decortication of thickened parietal and visceral pleura was performed. Afterward, the baby showed quick and progressive clinical improvement. Conclusion. The diagnosis and management of empyema in neonates may be challenging, especially in the case of unremarkable history, fulminant progression of the disease, and incomplete imaging tests.
Keywords: diagnosis; infant, newborn; empyema, pleural; sepsis; thoracic surgical procedures; tomography, x-ray computed